Implementation of hybrid learning in learning package C equivalency in learning activities center - A'ida, Maya Sahila; Shofwan, Imam (Edukasi, 2023)
Change system learning in this era of revolution 4.0 more utilise availability technology information and the internet, especially during covid-19. Online learning that took place during the Covid-19 pandemic shocked the world of education , because Lots society that hasn't Ready facing the era of revolution 4.0. For overcome problem said , done effort management hybrid learning . Hybrid learning combines activity learning stare advance with learning internet based . Study This use approach qualitative . Data collection techniques use method interviews , documentation , and observations . Data analysis techniques using technique proposed by Miles and Huberman, viz data collection , data reduction , presentation , and conclusions . Research result This show that hybrid learning consisting of from (1) Planning prepared and planned moreover formerly like compile module , and how implementation hybrid learning ; (2) Implementation done with combine activity stare face to face and online; (3) Evaluation learning in the Studio Learning Activities (SKB) Banjarnegara has held with good and smooth . Implications from study This is education equality package C is expected can facilitate participant students who have desire For continue education when Already own work.